2007
DOI: 10.1163/156939307783152957
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Analysis of Large-Scale Periodic Structures Using the Sub-Entire Domain Basis Function Method and Characteristic Function Method

Abstract: In this paper, the sub-entire domain basis function method and characteristic function (CF) method are used to analyze scattering of large-scale periodic structures. The former can dramatically reduce the number of unknows. To reduce the time for impedance matrix generation, the CF method can be used when the distance between the source function and the testing function positions is big enough. Finally, some simulation examples are given to validate the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Similar to the process in Ref. [10,14,[22][23][24][25][26], by describing the fields with two Bromwich scalar potentials Φ TE and Φ TM and applying the boundary conditions, the scattered potentials can be obtained as:…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the process in Ref. [10,14,[22][23][24][25][26], by describing the fields with two Bromwich scalar potentials Φ TE and Φ TM and applying the boundary conditions, the scattered potentials can be obtained as:…”
Section: Introductionmentioning
confidence: 99%
“…But because the BIE method is used on the boundary, the number of non-zero elements in the final matrix equation of the FDFD-BIE method rises rapidly, when a large object, such as a large array, is analyzed. The subentire-domain (SED) basis functions for the MoM were proposed [6,7] and used to analyze large finite periodic metal arrays [8][9][10]. In this efficient technique, the periodic property is considered, and the mutual coupling is approximately treated, so the number of unknowns can be dramatically reduced.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, a CCITL possesses conjugate characteristic impedances Z ± 0 of waves propagating in the opposite directions along the transmission line. Examples of CCITLs are reciprocal lossless uniform TLs, nonreciprocal lossless uniform TLs [8][9][10], exponentially tapered lossless nonuniform TLs [2,11,12] and periodically loaded lossless TLs operated in passband [13][14][15][16][17][18]. Using the ABCD matrix technique, it can be shown that the equation of the input impedance at each terminal of loaded finite lossless periodic structures is in the same form as that of CCITLs [4].…”
Section: Introductionmentioning
confidence: 99%